2019
DOI: 10.12998/wjcc.v7.i22.3866
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of gastric duplication cyst by positron emission tomography/computed tomography: A case report

Abstract: BACKGROUNDGastric duplication cysts (GDCs) are extremely uncommon lesions and the definitive diagnosis of GDCs is challenging for gastrointestinal specialists. It is important that a differential diagnosis is performed to rule out the possibility of other diseases, mainly malignancies with a cystic component. Despite the use of multiple diagnostic modalities including endoscopy, the preoperative diagnosis of GDCs is challenging.CASE SUMMARYA 53-year-old female patient with a GDC was confirmed by positron emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…There is a higher risk of confusion with the latter method, and the challenge arises from the difficulty in discerning between cystic formations with varying contents. On the other hand, this does not seem to be the case for F-FDG-PET/CT [26]. Mohamad Abdalkader et al presented the case of a 28-year-old adult who reported persistent abdominal pain and nausea [18].…”
Section: Discussionmentioning
confidence: 97%
“…There is a higher risk of confusion with the latter method, and the challenge arises from the difficulty in discerning between cystic formations with varying contents. On the other hand, this does not seem to be the case for F-FDG-PET/CT [26]. Mohamad Abdalkader et al presented the case of a 28-year-old adult who reported persistent abdominal pain and nausea [18].…”
Section: Discussionmentioning
confidence: 97%
“…The gases and liquids are observed in the gastric cavity, indicating that the opening of the diverticulum is connected with the gastric cavity. Gastric duplication cyst is an extremely uncommon lesion, which is common in infants and sometimes accompanied by other malformations [ 37 ]. Ménétrier disease usually presents with thickened gastric folds, but without cystic changes.…”
Section: Discussionmentioning
confidence: 99%
“…En la paciente presentada, de acuerdo con los hallazgos ecográficos iniciales, se realizó una tomografía computarizada de abdomen, para caracterizar mejor la lesión, con la presunción de un tumor del estroma gastrointestinal versus una neoplasia maligna de origen epitelial como diagnóstico diferencial. En relación con el diagnóstico, la literatura reporta mayor rendimiento de métodos como biopsia por aspiración con aguja fina guiada por endoscopia o endosonografía, y la tomografía por emisión de positrones (PET-CT), en comparación con la tomografía computarizada o la resonancia magnética nuclear 13,18,19 . En este caso no se consideró la realización de PET-CT o la biopsia por endosonografía debido a que estas opciones no están disponibles en nuestro medio, no existe evidencia que apoye su uso, su costo es elevado y no afectaba la decisión del manejo quirúrgico.…”
Section: Discussionunclassified